种碳基复合电极材料及其制备方法 (2018)
本发明公开了种碳基复合电极材料及其制备方法；以低聚酚醛树脂Resol和氧化石墨烯为碳源前驱体，三嵌段共聚物P123和F127为双模板剂，通过水热法制备多级孔碳-石墨烯复合块体材料。所得材料具有微孔-介孔-大孔的多级孔结构、高的比表面积、大的孔容。作为超级电容器电极材料时表现出高的比容量、良好的速率容量以及优异的循环稳定性能。本发明制备方法简单易行，成本低，易于进行工业化生产，所得产品在超级电容器领域具有巨大的应用前景。 The invention discloses a carbon-based composite electrode material and a preparation method thereof. The hierarchical pore carbon-graphite composite bulk material is prepared by a hydrothermal method with oligo-phenolic resin Resol and graphene oxide as carbon source precursors and triblock copolymers P123 and F127 as dual templates. The obtained material has a microporous/mesoporous/macroporous hierarchical pore structure, a high specific surface area, and a large pore volume. The material exhibits high specific capacity, good rate capacity and excellent cycle stability when used as a supercapacitor electrode material. The preparation method disclosed by the invention has the advantages of simple and easy process, low cost and easiness for industrial production, and the obtained product has great ap